2006
DOI: 10.1007/s10573-006-0089-4
|View full text |Cite
|
Sign up to set email alerts
|

Detonation waves in a reactive supersonic flow

Abstract: A supersonic hydrogen-air flow is studied in detail, in particular, the fields of gasdynamic parameters and chemical homogeneity of the mixture in various cross sections of the duct. The processes of excitation and propagation of a detonation wave in the downstream and upstream directions are considered. The detonation-wave velocity with respect to the mixture flow is found to differ from the nominal Chapman-Jouguet velocity for a quiescent mixture: the detonation-wave velocity is higher if the wave moves upst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Currently available experimental stud- ies [6,9,3] have confirmed that detonation waves could propagate upstream through combustible supersonic flow in the duct. It indicates that PNDWE is feasible in principle.…”
Section: Introductionmentioning
confidence: 97%
“…Currently available experimental stud- ies [6,9,3] have confirmed that detonation waves could propagate upstream through combustible supersonic flow in the duct. It indicates that PNDWE is feasible in principle.…”
Section: Introductionmentioning
confidence: 97%
“…al. [5]. The performance of single phase detonation engine using divergent nozzle at the exit section of detonation tube was studied using CFD [6].…”
Section: Introductionmentioning
confidence: 99%
“…Wintenberger & Shepherd (2003), Wintenberger (2004), Vasil'ev, Zvegintsev & Nalivaichenko (2006) and Zhuravskaya & Levin (2012). Wintenberger (2004) carried out a detailed investigation of applications of detonative combustion to propulsion.…”
Section: Introductionmentioning
confidence: 99%
“…These include the necessity of using high-enthalpy flows of fuel-oxidizer mixture, careful control of expansion in the divergent part of the nozzle to avoid fuel condensation that occurs at low temperatures, control of the mixing distance to avoid premature combustion ahead of the detonation shock, etc. In Vasil'ev et al (2006), detonation in a supersonic flow in a channel was studied experimentally. A supersonic stream of a fuel-air mixture was generated with the help of high-pressure supply tanks pushing the fuel and oxidizer through a convergent-divergent nozzle into the test channel.…”
Section: Introductionmentioning
confidence: 99%